Synthesis and Properties of Two Novel Ru(phen)2+3-based Probes for Electrochemiluminescent Immunoassay - Wang, Peng; Zhu, Guoyi (Asian Journal of Chemistry, 2010)
Two novel Ru(phen)2+3-based probes for electrochemiluminescent immunoassay, Ru(phen)2(phen-NHCOCH2CH2COOH)(PF6)2 and Ru(phen)2 (phen-NHCOCH2CH2CH2COOH)(PF6)2, were designed, synthesized and characterized. Electrochemistry, Fluorescence, and electrochemiluminescence of the two complexed are also reported.